Optimasi Level Benzyl Amino Purin (BAP) terhadap Pertumbuhan Tanaman Kembang Telang (Clitoria ternatea) melalui Teknik Kultur Jaringan: Optimization of Benzyl AminoPurin (BAP) Levels for the Growth of Butterfly Pea (Clitoria ternatea) Plants through Tissue Culture Techniques - Jannah, Kennaya Putri Aura; Prihantoro, Iwan; karti, panca dewi manu hara (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
The research objective was to measure the optimum level of BAP for supporting the growth of butterfly pea flowers through tissue culture techniques. The study used a completely randomized design (CRD) with 5 treatments based on BAP media levels (BAP 0 ppm, BAP 0.5 ppm, BAP 1 ppm, BAP 1.5 ppm, and BAP 2 ppm) and 20 replications. Parameters measured were plant height, plant height increase, number of leaves, number of branches, number of tillers, percentage of tiller growth, plant weight, and leaf color. The results showed that the use of BAP levels 0, 0.5, 1, 1.5, and 2 ppm in butterfly pea flower plants through tissue culture techniques was not effective in increasing plant height, number of leaves, number of branches, number of tillers, and percentage of tillers at the end of the research (27 DAP). Using an optimum BAP level of 0.5 ppm resulted in higher biomass production and the dominance of green leaf color visualization. Key words: BAP (Benzyl Amino Purine), butterfly pea, Clitoria ternatea, tissue culture